Serum Interleukin- 6, Tumor Necrosis Factor-α, D-Dimer after recombinant human brain natriuretic peptide combined with levosimendan in patients with heart failure : serum markers after heart failure treatment - Zhang, Yujing (Journal of Medical Biochemistry, 2025)
Aim: This study focused on the effects of recombinant human brain natriuretic peptide combined with levosimendan on the efficacy and Interleukin- 6, Tumor Necrosis Factor-α, D-Dimer of patients with heart failure. Methods: This study included 162 patients who were treated for heart failure from March 2022 to March 2024 in our hospital. Randomly divided into three groups, all three groups were given conventional treatment plus nutritional therapy, one group was given recombinant human brain natriuretic peptide treatment on this basis, the second group was given levosimendan treatment on this basis, the third group was given recombinant human brain natriuretic peptide and levosimendan combination treatment. The treatment efficacy, cardiac function, renal function, inflammatory factors, nutritional status and quality of life of patients in the three groups were compared. Results: The results indicated that all three groups could improve the patients’ efficacy, cardiac and renal function and nutritional status, inhibited the development of inflammatory factors and improved the quality of life, with the most significant improvement in combination group. IL-6 and TNF-α were notably lower than before and tended to be in the normal range after treatment in the three groups. The effect of TG on inflammation was the most notable(P < 0.05), ALB, TP, HGB and MNA levels were notably higher after treatment than before treatment in all groups (P < 0.05). Conclusion: IN conclusion, recombinant human brain natriuretic peptide combined with levosimendan treatment based on nutritional support can effectively improve the efficacy, nutritional status and quality of life of patients with heart failure.